Gas exchange model using heterogeneous diffusivity to study internal browning in ‘Conference’ pear - Nugraha, Bayu; Verboven, Pieter; Verlinden, Bert E.; Verreydt, Celine; Boone, Matthieu; Josipovic, Iván; Nicolaï, Bart M. (Postharvest biology and technology, 2022)
Internal gas gradients in pear fruit during controlled atmosphere storage depend on the effective gas diffusivity of the tissue. The diffusivity varies over the fruit organ due to the heterogeneous tissue microstructure across the fruit. This study implemented effective diffusivity maps reflecting the heterogeneous structure to predict internal gas gradients and relate the result to the occurrence of internal browning. Diffusivity maps of different pears were calculated from X-ray CT based porosity maps. Internal oxygen (O2), carbon dioxide (CO2) and respiratory quotient (RQ) levels were computed using a reaction-diffusion model incorporating the heterogeneous effective diffusivity map. Critical O2 and RQ levels for the shift from respiration to fermentation were defined based on the respiratory-fermentative energy balance of the cells. The model was indirectly validated by comparing RQ level contours with non-destructive 3D images of the internal browning of the pears after storage at 1.0 kPa and 0.5 kPa O2, combined with 0.7 kPa CO2 at 1 °C. The distribution of the internal gas concentrations and RQ was affected by the heterogeneity of the diffusivity. The results also confirmed the incidence of internal browning when the O2 and RQ were under or above critical O2 and RQ limits, respectively. The fermentation process was indicated to be dominant when the tissue’s RQ limit (RQ*) went above 2.12 (or at 0.044 kPa O2). The tissue volumes where O2 and RQ levels were critical corresponded reasonably well to browning-affected tissues of pears with different shapes. The pear with more shallow gas gradients showed less symptoms of browning. •Pear tissue microstructure was imaged using X-ray CT.•Heterogeneous gas diffusivity maps were derived from spatial porosity profiles.•Internal gas concentrations in pear were computed using heterogeneous diffusivity.•Pear tissue subject to energy deficiency corresponded to actual browning patches.